Diurnal Effects of Elevated CO2 and Reduced Soil Water Availability on Leaf Physiology and Water Relations - Shaw, Jodi R.; Renner, Otto Max (My University, 2010)
Increasing atmospheric CO2 concentrations and temperatures have led to shifts in precipitation patterns. An incomplete understanding of leaf physiological responses to these factors hinders our ability to accurately predict vegetation responses to global change. Our study examined plant water relations and leaf net photosynthesis under elevated CO2and how these responses are modulated by water availability and time of day.
Interactive Effects of Elevated CO2 and Reduced Soil Water Availability on Leaf Physiology and Water Relations
Color poster with text, images, and graphs.
Keywords: Leaves--Physiology--Effect of atmospheric carbon dioxide on; Leaves--Physiology--Effect of water levels on; Plant-water relationships--Effect of atmospheric carbon dioxide on; Plant-water relationships--Effect of water levels on; Posters